The effectiveness of Acceptance and Commitment Therapy on parental stress in parents of special children: a meta-analysis - Ying Guo; Haoran He; Jiajun Lan (Child and Adolescent Psychiatry and Mental Health)
Abstract Purpose Through a meta-analysis, this study evaluated the effectiveness of Acceptance and Commitment Therapy (ACT) in reducing stress among parents of children with special needs. This study aimed to quantify the intervention effect and identify moderating variables, such as cultural differences and intervention parameters, to provide evidence for clinical practice. Methods Systematic searches were conducted across the ​​PsycINFO​​, PubMed, Web of Science, and Cochrane Library databases. The inclusion criteria were as follows: (1) peer-reviewed English publications; (2) randomized controlled trials; (3) the use of ACT as the core intervention; (4) study participants being parents of children with special needs; and (5) reporting standardized effect sizes for stress symptoms. A total of 10 studies (n = 700) met the inclusion criteria. A random effects model was employed for the meta-analysis, and subgroup analyses were performed based on geographic distribution, intervention duration, intervention parameters, and types of children’s illnesses (neurodevelopmental disorders, chronic diseases, and critical conditions). Results ACT significantly reduced stress symptoms among parents of special children, with a standardized mean difference (SMD =– 0.42, 95% CI– 0.72 to– 0.12, P = 0.0068). Subgroup analyses and meta-regression indicated a notable non-linear dose-response relationship concerning the intervention parameters. Key factors contributing to the heterogeneity of intervention outcomes included the frequency of the intervention, duration per session, overall intervention period, modalities employed, types of parental groups, and categories of children’s illnesses. Conclusion ACT demonstrated moderate efficacy in alleviating stress among parents of exceptional children. The most significant stress reduction was observed when interventions were conducted for a minimum of 120 min per session, at least twice weekly, and over a total duration exceeding 8 weeks, particularly when ACT was integrated with other interventions for parents of children suffering from chronic and critical illnesses. Additionally, the effectiveness of the intervention in mixed-gender parent groups was significantly greater than in groups where mothers constituted over 90% of participants (P < 0.05). Implementing high-intensity ACT courses for populations experiencing acute stress is recommended to facilitate the rapid alleviation of stress symptoms. Concurrently, mobile health-assisted, low-density, long-term interventions are suggested for individuals dealing with chronic stress. Future research should investigate the efficacy disparities in predominantly mother-led groups and strive to develop gender-adapted ACT protocols.